KRITIK SOSIAL DALAM NOVEL TERUSLAH BODOH JANGAN PINTAR KARYA TERE LIYE - Akbar, Dandi; Suyuthi, Hasmi; Lisdayanti, Septina; Yuniati, Ira (Universitas Sultan Ageng Tirtayasa, 2025)
The problem of this research is social criticism in the novel Teruslah Bdoh Jangan Pintar by Tere Liye. This research aims to get a precise, detailed, and in-depth description of the social criticism in the novel Teruslah Bdoh Jangan Pintar by Tere Liye. This research uses qualitative descriptive method. The data in this study are words, sentences and paragraphs that contain social criticism in the novel Teruslah Bodoh Jangan Pintar by Tere Liye. The data collection technique in this research uses literature study technique. The results of the research found social criticism: (1) social criticism of political issues (2) social criticism of poverty issues, and 3) social criticism of environmental issues. The conclusion from the results and discussion is that, this research criticizes three aspects, namely social criticism on politics, social criticism on poverty issues and social criticism on environmental issues.